Phytochemical Screening and α-glucosidase Inhibitory of Secang Wood (Caesalpinia sappan L.) - Ahmad, Aktsar Roskiana; Islamia, Tiara Katulista; Amin, Asni (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Secang wood (Caesalpinia sappan L.) is a part of the Secang plant which is widely used to treat various diseases, including diabetes. Based on previous research, secang wood contains flavonoids which have the potential to inhibit the α-glucosidase enzyme. The research aims to determine the potential of ethanol extracted by meseration using 96% ethanol. Inhibition of activity was tested using microplate reader which was measured at a wavelength of 405 nm with acarbose as a comparison. The results of the research show that the ethanol extract of secang wood has inhibitory activity, including it in the active category based on the % inhibition value obtained at 83.63%. Meanwhile, acarbose has inhibitory activity, including it in the very active category with a %inhibition value of 79%.